2021
DOI: 10.3390/toxins13050309
|View full text |Cite
|
Sign up to set email alerts
|

Ageratina adenophora Inhibits Spleen Immune Function in Rats via the Loss of the FRC Network and Th1–Th2 Cell Ratio Elevation

Abstract: The objective of this study was to determine the impact of Ageratina adenophora (A. adenophora) on splenic immune function in a rat model. Rats were fed with 10 g/100 g normal feed and an experimental feed, which was composed of 3:7 A. adenophora powder and normal feed for 60 days. On days 14, 28, and 60, subsets of rats (n = 8 rats/group/time point) were selected for blood and spleen tissue sample collection. The results showed that the proportion of CD3+ T cells in the spleen was decreased at day 60 (vs. con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The experimental period was 60 days. The dose of the A. adenophora powder used in this experiment was based on a pilot experiment that indicated that feeding mice with a mixture of 30% A. adenophora leaf powder and 70% basal diet for a period of 60 days did not affect feed intake [ 64 , 65 ]. Throughout the experiment, drinking water was provided to rats ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental period was 60 days. The dose of the A. adenophora powder used in this experiment was based on a pilot experiment that indicated that feeding mice with a mixture of 30% A. adenophora leaf powder and 70% basal diet for a period of 60 days did not affect feed intake [ 64 , 65 ]. Throughout the experiment, drinking water was provided to rats ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry assay was carried out as described by Ren et al [ 40 ]. After incubation, cells were analyzed in a FACScalibur flow cytometer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…The exposure of animals to A. adenophora causes an elevation in reactive oxygen species (ROS) parameters, such as nitric oxide, superoxide and hydroxyl radicals, leading to the damage of DNA and proteins in addition to altering the cellular architecture, permeability and cell survival [ 32 , 33 ]. A. adenophora is reported to trigger a series of downstream signaling cascades and further interrupt signaling pathways associated with cell growth, proliferation and apoptosis [ 3 ].…”
Section: Molecular Mechanism Of a Adenophora Toxicitymentioning
confidence: 99%
“…Another current research reported that A. adenophora causes toxicity in the spleen by destroying the fibroblastic reticular cell (FRC) network and causing an imbalance in the Th1–Th2 cell ratio [ 33 ]. The study speculated that A. adenophora ingestion induces a persistent inflammatory response in the spleen, which in turn could lead to the activation and promotion of T cell immunity, resulting in splenic dysfunction.…”
Section: Molecular Mechanism Of a Adenophora Toxicitymentioning
confidence: 99%